Impact of vitamin C on the reduction of opioid consumption for acute musculoskeletal pain: A double-blind randomized control pilot study. - Raoul Daoust; Jean Paquet; David Williamson; Vérilibe Huard; Caroline Arbour; Jeffrey J Perry; Marcel Émond; Simon Berthelot; Patrick Archambault; Dominique Rouleau; Judy Morris; Alexis Cournoyer (PLoS ONE)
Introduction Recent evidence has shown that vitamin C has analgesic and opioid sparing properties in immediate postoperative context. However, this has never been studied for acute musculoskeletal (MSK) emergency department (ED) injuries. The aim of this pilot study is to evaluate the feasibility of conducting a randomized placebo-controlled study to determine the opioid sparing and analgesic effect of vitamin C compared to placebo, in acute MSK injured ED patients. Methods A double-blind randomized controlled trial (RCT) distributed in two arms, stratified for fractures, was performed in a tertiary care center, one group receiving 1 g of vitamin C twice a day for 14 days and another receiving placebo. Participants were ≥18 years of age, treated in ED for MSK injuries present for ≤2 weeks, and discharged with a standardized opioid prescription of 20 morphine 5 mg tablets (M5T) and, at the clinician discretion, 28 tablets of naproxen 500 mg. Participants completed a 14-day paper diary and were contacted by phone at 14 days, to document their analgesic use, vitamin C consumption, and pain intensity. Results Overall, 137 patients were screened; 44(32%) were excluded, 38(40.9%) refused, leaving 55(59.1%) participants, with a consent rate of 9.2/month. Mean age was 53 years (SD = 16) and 55% were men. Fourteen (25%) participants were lost to follow-up and 33(83%) patients complied with treatment. For per-protocol analysis, the median (IQR) M5T consumed was 6.5 (3.3-19.5) for the vitamin C and 9.0 (1.5-16.0) for placebo group. The median (IQR) naproxen 500 mg tablets consumed was 0 (0-9.8) for the vitamin C group and 20 (0-27) for the placebo arm. Conclusion This pilot study supports the feasibility of a larger RCT on the opioid sparing and analgesic properties of vitamin C for acute MSK injured ED patients. Strategies to reduce the refusal and lost to follow-up rates are discussed. Trial registration number NCT05555576, ClinicalTrials.Gov PRS.